2011
DOI: 10.1038/jid.2010.277
|View full text |Cite
|
Sign up to set email alerts
|

IL-25 in Atopic Dermatitis: A Possible Link between Inflammation and Skin Barrier Dysfunction?

Abstract: Atopic dermatitis (AD) is a common skin disease associated with a T(H)2 response and increased levels of T(H)2-associated cytokines and IgE. The mechanisms resulting in skewing the immune response in a T(H)2 direction in AD are not fully elucidated. However, such skewing has recently been associated with IL-25 in a murine model for allergic airway disease. The aim of this study was to investigate whether IL-25 may have a role in AD. We have identified IL-25-producing cells within the dermis of AD patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
172
2
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(191 citation statements)
references
References 30 publications
10
172
2
7
Order By: Relevance
“…Increased transcripts encoding IL-33 and IL-25 were also detected in the cells in acute lesional atopic dermatitis skin as compared with control subjects, and in vitro cultured human ILC2 released type-2 cytokines and amphiregulin in response to IL-33 stimulation. These data are consistent with the elevated IL33 mRNA reported previously in the lesional skin of patients with AD and, similarly, the detection of higher levels of IL-25 in patients with AD (46)(47)(48). Notably, IL-33, and to a lesser extent TSLP (but not IL-25), induced migration of skin-derived human ILC2 (45,49).…”
Section: Ilc2 In Skin Allergysupporting
confidence: 81%
“…Increased transcripts encoding IL-33 and IL-25 were also detected in the cells in acute lesional atopic dermatitis skin as compared with control subjects, and in vitro cultured human ILC2 released type-2 cytokines and amphiregulin in response to IL-33 stimulation. These data are consistent with the elevated IL33 mRNA reported previously in the lesional skin of patients with AD and, similarly, the detection of higher levels of IL-25 in patients with AD (46)(47)(48). Notably, IL-33, and to a lesser extent TSLP (but not IL-25), induced migration of skin-derived human ILC2 (45,49).…”
Section: Ilc2 In Skin Allergysupporting
confidence: 81%
“…IL-25 increases the expression of IL-5 and IL-13 in TSLP-DC-activated T cells (26). Immunohistochemical staining showed increased IL-25 + keratinocytes in AD lesions, as compared to nonlesional skin (27). There was also an increased infiltration of cells, which expressed IL-17Rh1, an IL-25 receptor, in AD lesions, as compared to nonlesional AD skin (27).…”
Section: Keratinocyte Dysfunctions In Admentioning
confidence: 77%
“…Immunohistochemical staining showed increased IL-25 + keratinocytes in AD lesions, as compared to nonlesional skin (27). There was also an increased infiltration of cells, which expressed IL-17Rh1, an IL-25 receptor, in AD lesions, as compared to nonlesional AD skin (27). However, the majority of IL-25 producers are likely DC, eosinophils, and basophils (26,27).…”
Section: Keratinocyte Dysfunctions In Admentioning
confidence: 99%
“…Numerous studies have demonstrated that several inflammatory mediators (e.g., IL4, IL13, IL25, IL17A and histamine) affect keratinocyte differentiation, most often leading to impaired barrier formation. [72][73][74][75] Studies on noncutaneous epithelium have established that inflammatory mediators are involved in TJ assembly and disassembly during inflammatory conditions, 76 and also in keratinocytes an influence of several cytokines on TJ proteins/function was described (see below). Whether these mediators directly affect epidermal TJs or whether it is an indirect effect via altered differentiation is an active area of research.…”
Section: Tj and Adaptive Immune Barriermentioning
confidence: 99%